Investment efficiency of firms outside the business group - Liu, Yunxiao; Kim, Woochan; Sung, Taeyoon (Journal of Corporate Finance, 2021)
Using Korean firms between 1987 and 2010, we show that non-group firms suffer more from investment inefficiency if they operate in industries where group firms belong to larger business groups. We also find that this effect exists mainly during a period characterized by a capital supply shortage and low cash flow pledgeability to investors. Further analyses indicate that the effect is attributable not to human capital constraints, but external financing constraints imposed by business group firms and that causality runs from business group strength to investment inefficiency of non-group firms.